Congress of Neurological Surgeons essential papers in neurosurgery - El Tecle, Najib E.; El Ahmadieh, Tarek Y.; Aoun, Salah G.; Bendok, Bernard R.; Congress of Neurological Surgeons (New York, NY : Oxford University Press, 2020)
This text presents a collection of critically appraised neurosurgical papers that shed light on some of the most impactful studies in the history of neurosurgery. Papers that have shaped the practice of neurosurgery as we know it today have been selected for review. Each paper is reviewed by a panel of experts who evaluate the strengths and weaknesses of the paper as well as the impact it had on their personal practice of neurosurgery. The work is suited for residents and practicing neurosurgeons. The body of literature covered in this book has in many ways defined the gold standards of neurosurgical practice and is a must-know for every student of neurosurgery.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 25, 2020).
Keywords: Neurosurgery